PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PROFITABILITAS TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Hasby Hamyat; Sahyunu Sahyunu; Herman Titop; Asri Djauhar (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This study aims to determine the effect of corporate social responsibility and profitability on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample in this study were manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period, totaling 20 companies. This study uses multiple linear regression analysis as an analytical tool. The results of the study found that simultaneously CSR and profitability variables had a positive and significant effect on earnings quality. Partially, CSR has a negative and significant effect on the performance of BNN employees on earnings quality, while profitability has a positive and insignificant effect on earnings quality.